Gone With the Wool. - Hechtman, Betty, 1947- (Hechtman, Betty, 1947- Yarn retreat mysteries., 2016)
Every October, thousands of monarch butterflies flock to California's Monterey Peninsula to spend the winter there. To welcome their colorful guests, Cadbury by the Sea holds a weeklong festival complete with a butterfly queen and her court. Eager to show some town spirit, Casey Feldstein finds herself fluttering back and forth between setting up a yarn retreat, baking and helping out at the festival. But when a former butterfly queen is found dead with a knife in her back after a Bless the Butterflies service, Casey must set her loom aside to hook a killer with a score to settle.